Opposite effects of tissue inhibitor of metalloproteinases-1 (TIMP-1) over-expression and knockdown on colorectal liver metastases - Bandapalli, Obul Reddy; Paul, Eva; Schirmacher, Peter; Brand, Karsten (BMC Research Notes, 2012)
Tissue inhibitors of metalloproteinases (TIMPs) and the corresponding metalloproteinases are integral parts of the protease network and have been shown to be involved in cancer development and metastasis. Paradoxically, for TIMP-1, tumor promoting as well as tumor inhibitory effects have been observed.